Rejection of organic micro-pollutants from water by a tubular, hydrophilic pervaporative membrane designed for irrigation applications - Sule,MN; Templeton,MR; Bond,T (Environmental Technology, 2016)
The links between chemical properties, including those relating to molecular size, solubility,hydrophobicity and vapour pressure, and rejection of model aromatic micro-pollutants by atubular, hydrophilic polymer pervaporation membrane designed for irrigation applicationswas investigated. Open air experiments were conducted at room temperature for individualsolutions of fluorene, naphthalene, phenol, 1,2-dichlorobenzene, 1,2-diethylbenzene and 2-phenoxyethanol. Percentage rejection generally increased with increased molecular size forthe model micro-pollutants (47% - 86%). Molecular weight and logKow had the strongestpositive relationships with rejection, as demonstrated by respective correlation coefficients ofr = 0.898 and 0.824. Rejection was also strongly negatively correlated with aqueoussolubility and H-bond δ. However, properties which relate to vapour phase concentrations ofthe micro-pollutants were not well correlated with rejection. Thus, physicochemicalseparation processes, rather than vapour pressure, drives removal of aromatic contaminantsby the investigated pervaporation tube. This expanded knowledge could be utilised inconsidering practical applications of pervaporative irrigation systems for treating organiccontaminatedwaters such as oilfield produced waters.